Low-Dose Naltrexone-Induced Remission in Hailey–Hailey Disease Maintained in Remission with Topical Combination of Ketamine and Diphenhydramine - Sonthalia, Sidharth (Indian Dermatol Online J, 2019)
Recent anecdotal evidence suggests that oral low-dose naltrexone (LDN) is effective for Hailey–Hailey disease (HHD) but suffers the limitation of immediate relapse following cessation of the medication. With lack of safety data on long-term administration of LDN, we explored the utility of a topical diphenhydramine/ketamine (DK) cream in maintaining the remission achieved with LDN. A 42-year-old male with treatment-refractory HHD remitted with 5 mg naltrexone/day but relapsed on stopping the drug. Symptoms abated after restarting LDN. The impact of regular twice-a-day application of a specially formulated DK cream containing diphenhydramine (2% w/w) and ketamine (1% w/w) over the affected areas on maintenance of remission was explored till the next relapse. Our approach enabled dose reduction of naltrexone to 3 mg/day without loss of treatment benefit. After 3-month overlap of naltrexone and DK cream, withdrawal of naltrexone maintained remission with only the topical regime with no adverse effects till 4 months of follow-up. The use of topical agents with anti-inflammatory, antipruritic, antinociceptive, and naltrexone-mimicking properties merits exploration as an option to provide short but significant period of naltrexone-free maintenance of remission to patients with HHD.